Dracontius as propagandist and historian: Didactic meaning of Roman history in De Laudibus Dei - I. M. Nikolsky (Шаги, 2023)
This article deals with the problem of interpreting the third book of the poem ‘Praises of God” (De Laudibus Dei) by the late antique Carthaginian poet Blossius Aemilius Dracontius. Since the poem is formally of theological character, researchers usually regard it as a Christian anti-pagan manifesto. However, comparison with other works by Dracontius, including the epyllia ‘The Abduction of Helen’ (De Raptu Helenae), ‘The Tragedy of Orestes’ (Orestis Tragoedia), and ‘Medea”, as well as ‘The Atonement’ (Satisfactio), written in prison as a verse plea for mercy, allows us to see in it political allegories that highlight other challenges relevant to the author’s contemporary period. In particular, Dracontius has in mind the collapse of the Roman Empire and the emergence of barbarian kingdoms, the associated redistribution of spheres of inﬂuence, and the struggle for power between the old and new elites. Manipulating textbook historical and mythological plots, the Roman poet constructs a didactic model focused on both of these groups in the Vandal kingdom, one that allows him to consider himself a signiﬁcant political inﬂuencer. The conclusions of the article shed light on the relationship between the “intellectual” Roman and the “military” Vandal noble groups in North Africa at the turn of the 5th and 6th centuries.